Study of adsorption of household gas molecules on electrophysical properties of porous silicon - Kogdas, Maksym (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2024)
Purpose. This research comprehensively investigates the adsorption of household gas molecules on porous silicon surfaces and its impact on the electrophysical properties of the material. The primary aim is to understand how the adsorption process influences the electrical conductivity and capacitance of porous silicon. Methodology. The study employs various electrophysical analysis methods to measure changes in the material’s conductivity and capacitance caused by gas adsorption. Furthermore, the research explores optimal conditions for detecting household gas and establishes the correlation between the degree of adsorption and alterations in electrophysical parameters. Originality. The research contributes novelty by not only revealing increased conductivity due to adsorption but also significant changes in capacitance, providing a foundation for developing efficient gas sensors. Additionally, the article discusses the potential applications of porous silicon in developing novel materials for gas sensors to detect various airborne pollutants. Results. In addition to the previously mentioned findings, the article highlights the results of experiments studying the influence of different concentrations of household gas on the electrophysical characteristics of porous silicon. This insight refines optimal parameters for the effective detection of gas pollutants. The research also discusses the applicability of the results in producing environmentally friendly and highly efficient sensor systems. Practical Value. The obtained conclusions deepen our understanding of the interaction between porous silicon and household gas, crucial for advancing gas sensor technologies. The study opens broad possibilities for applying porous silicon in highly sensitive and reliable gas sensors for diverse practical applications, including safety monitoring and air quality control in industrial and domestic settings. The practical implications extend to the development of real-time, eco-friendly sensor systems.